6.7: Exponential and Logarithmic Equations
 Page ID
 1510
\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)
\( \newcommand{\vecd}[1]{\overset{\!\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)
Skills to Develop
 Use like bases to solve exponential equations.
 Use logarithms to solve exponential equations.
 Use the definition of a logarithm to solve logarithmic equations.
 Use the onetoone property of logarithms to solve logarithmic equations.
 Solve applied problems involving exponential and logarithmic equations.
In 1859, an Australian landowner named Thomas Austin released \(24\) rabbits into the wild for hunting. Because Australia had few predators and ample food, the rabbit population exploded. In fewer than ten years, the rabbit population numbered in the millions.
Figure \(\PageIndex{1}\): Wild rabbits in Australia. The rabbit population grew so quickly in Australia that the event became known as the “rabbit plague.” (credit: Richard Taylor, Flickr)
Uncontrolled population growth, as in the wild rabbits in Australia, can be modeled with exponential functions. Equations resulting from those exponential functions can be solved to analyze and make predictions about exponential growth. In this section, we will learn techniques for solving exponential functions.
Using Like Bases to Solve Exponential Equations
The first technique involves two functions with like bases. Recall that the onetoone property of exponential functions tells us that, for any real numbers \(b\), \(S\), and \(T\), where \(b>0\), \(b≠1\), \(b^S=b^T\) if and only if \(S=T\).
In other words, when an exponential equation has the same base on each side, the exponents must be equal. This also applies when the exponents are algebraic expressions. Therefore, we can solve many exponential equations by using the rules of exponents to rewrite each side as a power with the same base. Then, we use the fact that exponential functions are onetoone to set the exponents equal to one another, and solve for the unknown.
For example, consider the equation \(3^{4x−7}=\dfrac{3^{2x}}{3}\). To solve for \(x\), we use the division property of exponents to rewrite the right side so that both sides have the common base, \(3\). Then we apply the onetoone property of exponents by setting the exponents equal to one another and solving for \(x\):
\[\begin{align*} 3^{4x7}&= \dfrac{3^{2x}}{3}\\ 3^{4x7}&= \dfrac{3^{2x}}{3^1} \qquad \text{Rewrite 3 as } 3^1\\ 3^{4x7}&= 3^{2x1} \qquad \text{Use the division property of exponents}\\ 4x7&= 2x1 \qquad \text{Apply the onetoone property of exponents}\\ 2x&= 6 \qquad \text{Subtract 2x and add 7 to both sides}\\ x&= 3 \qquad \text{Divide by 3} \end{align*}\]
USING THE ONETOONE PROPERTY OF EXPONENTIAL FUNCTIONS TO SOLVE EXPONENTIAL EQUATIONS
For any algebraic expressions \(S\) and \(T\), and any positive real number \(b≠1\),
\[\begin{align} b^S=b^T\text{ if and only if } S=T \end{align}\]
How to: Given an exponential equation with the form \(b^S=b^T\), where \(S\) and \(T\) are algebraic expressions with an unknown, solve for the unknown.
 Use the rules of exponents to simplify, if necessary, so that the resulting equation has the form \(b^S=b^T\).
 Use the onetoone property to set the exponents equal.
 Solve the resulting equation, \(S=T\), for the unknown.
Example \(\PageIndex{1}\): Solving an Exponential Equation with a Common Base
Solve \(2^{x−1}=2^{2x−4}\).
Solution
\[\begin{align*} 2^{x1}&= 2^{2x4} \qquad \text{The common base is 2}\\ x1&= 2x4 \qquad \text{By the onetoone property the exponents must be equal}\\ x&= 3 \qquad \text{Solve for x} \end{align*}\]
Exercise \(\PageIndex{1}\)
Solve \(5^{2x}=5^{3x+2}\).
 Answer

\(x=−2\)
Rewriting Equations So All Powers Have the Same Base
Sometimes the common base for an exponential equation is not explicitly shown. In these cases, we simply rewrite the terms in the equation as powers with a common base, and solve using the onetoone property.
For example, consider the equation \(256=4^{x−5}\). We can rewrite both sides of this equation as a power of \(2\). Then we apply the rules of exponents, along with the onetoone property, to solve for \(x\):
\[\begin{align*} 256&= 4^{x5}\\ 2^8&= {(2^2)}^{x5} \qquad \text{Rewrite each side as a power with base 2}\\ 2^8&= 2^{2x10} \qquad \text{Use the onetoone property of exponents}\\ 8&= 2x10 \qquad \text{Apply the onetoone property of exponents}\\ 18&= 2x \qquad \text{Add 10 to both sides}\\ x&= 9 \qquad \text{Divide by 2} \end{align*}\]
How to: Given an exponential equation with unlike bases, use the onetoone property to solve it.
 Rewrite each side in the equation as a power with a common base.
 Use the rules of exponents to simplify, if necessary, so that the resulting equation has the form \(b^S=b^T\).
 Use the onetoone property to set the exponents equal.
 Solve the resulting equation, \(S=T\), for the unknown.
Example \(\PageIndex{2}\): Solving Equations by Rewriting Them to Have a Common Base
Solve \(8^{x+2}={16}^{x+1}\).
Solution
\[\begin{align*} 8^{x+2}&= {16}^{x+1}\\ {(2^3)}^{x+2}&= {(2^4)}^{x+1} \qquad \text{Write 8 and 16 as powers of 2}\\ 2^{3x+6}&= 2^{4x+4} \qquad \text{To take a power of a power, multiply exponents}\\ 3x+6&= 4x+4 \qquad \text{Use the onetoone property to set the exponents equal}\\ x&= 2 \qquad \text{Solve for x} \end{align*}\]
Exercise \(\PageIndex{2}\)
Solve \(5^{2x}={25}^{3x+2}\).
 Answer

\(x=−1\)
Example \(\PageIndex{3}\): Solving Equations by Rewriting Roots with Fractional Exponents to Have a Common Base
Solve \(2^{5x}=\sqrt{2}\).
Solution
\[\begin{align*} 2^{5x}&= 2^{\dfrac{1}{2}} \qquad \text{Write the square root of 2 as a power of 2}\\ 5x&= \dfrac{1}{2} \qquad \text{Use the onetoone property}\\ x&= \dfrac{1}{10} \qquad \text{Solve for x} \end{align*}\]
Exercise \(\PageIndex{3}\)
Solve \(5^x=\sqrt{5}\).
 Answer

\(x=\dfrac{1}{2}\)
Q&A: Do all exponential equations have a solution? If not, how can we tell if there is a solution during the problemsolving process?
No. Recall that the range of an exponential function is always positive. While solving the equation, we may obtain an expression that is undefined.
Example \(\PageIndex{4}\): Solving an Equation with Positive and Negative Powers
Solve \(3^{x+1}=−2\).
Solution
This equation has no solution. There is no real value of \(x\) that will make the equation a true statement because any power of a positive number is positive.
Analysis
Figure \(\PageIndex{2}\) shows that the two graphs do not cross so the left side is never equal to the right side. Thus the equation has no solution.
Figure \(\PageIndex{2}\)
Exercise \(\PageIndex{4}\)
Solve \(2^x=−100\).
 Answer

The equation has no solution.
Solving Exponential Equations Using Logarithms
Sometimes the terms of an exponential equation cannot be rewritten with a common base. In these cases, we solve by taking the logarithm of each side. Recall, since \(\log(a)=\log(b)\) is equivalent to \(a=b\), we may apply logarithms with the same base on both sides of an exponential equation.
How to: Given an exponential equation in which a common base cannot be found, solve for the unknown
 Apply the logarithm of both sides of the equation.
 If one of the terms in the equation has base 10, use the common logarithm.
 If none of the terms in the equation has base 10, use the natural logarithm.
 Use the rules of logarithms to solve for the unknown.
Example \(\PageIndex{5}\): Solving an Equation Containing Powers of Different Bases
Solve \(5^{x+2}=4^x\).
Solution
\[\begin{align*}
5^{x+2}&= 4^x \qquad \text{There is no easy way to get the powers to have the same base}\\
\ln5^{x+2}&= \ln4^x \qquad \text{Take ln of both sides}\\
(x+2)\ln5&= x\ln4 \qquad \text{Use laws of logs}\\
x\ln5+2\ln5&= x\ln4 \qquad \text{Use the distributive law}\\
x\ln5x\ln4&= 2\ln5 \qquad \text{Get terms containing x on one side, terms without x on the other}\\
x(\ln5\ln4)&= 2\ln5 \qquad \text{On the left hand side, factor out an x}\\
x\ln \left (\dfrac{5}{4} \right )&= \ln \left (\dfrac{1}{25} \right ) \qquad \text{Use the laws of logs}\\
x=\dfrac{\ln \left (\dfrac{1}{25} \right )}{\ln \left (\dfrac{5}{4} \right )} \qquad \text{Divide by the coefficient of x}
\end{align*}\]
Exercise \(\PageIndex{5}\)
Solve \(2^x=3^{x+1}\).
 Answer

\(x=\dfrac{\ln3}{\ln \left (\dfrac{2}{3} \right )}\)
Q&A: Is there any way to solve \(2^x=3^x\)?
Yes. The solution is \(0\).
Equations Containing \(e\)
One common type of exponential equations are those with base \(e\). This constant occurs again and again in nature, in mathematics, in science, in engineering, and in finance. When we have an equation with a base \(e\) on either side, we can use the natural logarithm to solve it.
How to: Given an equation of the form \(y=Ae^{kt}\), solve for \(t\).
 Divide both sides of the equation by \(A\).
 Apply the natural logarithm of both sides of the equation.
 Divide both sides of the equation by \(k\).
Example \(\PageIndex{6}\): Solve an Equation of the Form \(y = Ae^{kt}\)
Solve \(100=20e^{2t}\).
Solution
\[\begin{align*} 100&= 20e^{2t}\\ 5&= e^{2t} \qquad \text{Divide by the coefficient of the power}\\ \ln5&= 2t \qquad \text{Take ln of both sides. Use the fact that } ln(x) \text{ and } e^x \text{ are inverse functions}\\ t&= \dfrac{\ln5}{2} \qquad \text{Divide by the coefficient of t} \end{align*}\]
Analysis
Using laws of logs, we can also write this answer in the form \(t=\ln\sqrt{5}\). If we want a decimal approximation of the answer, we use a calculator.
Exercise \(\PageIndex{6}\)
Solve \(3e^{0.5t}=11\).
 Answer

\(t=2\ln \left (\dfrac{11}{3} \right )\) or \(\ln{ \left (\dfrac{11}{3} \right )}^2\)
Q&A: Does every equation of the form \(y=Ae^{kt}\) have a solution?
No. There is a solution when \(k≠0\),and when \(y\) and \(A\) are either both 0 or neither 0, and they have the same sign. An example of an equation with this form that has no solution is \(2=−3e^t\).
Example \(\PageIndex{7}\): Solving an Equation That Can Be Simplified to the Form \(y=Ae^{kt}\)
Solve \(4e^{2x}+5=12\).
Solution
\[\begin{align*} 4e^{2x}+5&= 12\\ 4e^{2x}&= 7 \qquad \text{Combine like terms}\\ e^{2x}&= \dfrac{7}{4} \qquad \text{Divide by the coefficient of the power}\\ 2x&= \ln \left (\dfrac{7}{4} \right ) \qquad \text{Take ln of both sides}\\ x&= \dfrac{1}{2}\ln \left (\dfrac{7}{4} \right ) \qquad \text{Solve for x} \end{align*}\]
Exercise \(\PageIndex{7}\)
Solve \(3+e^{2t}=7e^{2t}\).
 Answer

\(t=\ln \left (\dfrac{1}{\sqrt{2}} \right )=−\dfrac{1}{2}\ln(2)\)
Extraneous Solutions
Sometimes the methods used to solve an equation introduce an extraneous solution, which is a solution that is correct algebraically but does not satisfy the conditions of the original equation. One such situation arises in solving when the logarithm is taken on both sides of the equation. In such cases, remember that the argument of the logarithm must be positive. If the number we are evaluating in a logarithm function is negative, there is no output.
Example \(\PageIndex{8}\): Solving Exponential Functions in Quadratic Form
Solve \(e^{2x}−e^x=56\).
Solution:
\[\begin{align*} e^{2x}e^x&= 56\\ e^{2x}e^x56&= 0 \qquad \text{Get one side of the equation equal to zero}\\ (e^x+7)(e^x8)&= 0 \qquad \text{Factor by the FOIL method}\\ e^x+7&= 0 \qquad \text{or} \\ e^x8&= 0 \qquad \text{If a product is zero, then one factor must be zero}\\ e^x&= 7 \qquad \text{or} \\ e^x&= 8 \qquad \text{Isolate the exponentials}\\ e^x&= 8 \qquad \text{Reject the equation in which the power equals a negative number}\\ x&= \ln8 \qquad \text{Solve the equation in which the power equals a positive number} \end{align*}\]
Analysis
When we plan to use factoring to solve a problem, we always get zero on one side of the equation, because zero has the unique property that when a product is zero, one or both of the factors must be zero. We reject the equation \(e^x=−7\) because a positive number never equals a negative number. The solution \(\ln(−7)\) is not a real number, and in the real number system this solution is rejected as an extraneous solution.
Exercise \(\PageIndex{8}\)
Solve \(e^{2x}=e^x+2\).
 Answer

\(x=\ln2\)
Q&A: Does every logarithmic equation have a solution?
No. Keep in mind that we can only apply the logarithm to a positive number. Always check for extraneous solutions.
Using the Definition of a Logarithm to Solve Logarithmic Equations
We have already seen that every logarithmic equation \({\log}_b(x)=y\) is equivalent to the exponential equation \(b^y=x\). We can use this fact, along with the rules of logarithms, to solve logarithmic equations where the argument is an algebraic expression.
For example, consider the equation \({\log}_2(2)+{\log}_2(3x−5)=3\). To solve this equation, we can use rules of logarithms to rewrite the left side in compact form and then apply the definition of logs to solve for \(x\):
\[\begin{align*} {\log}_2(2)+{\log}_2(3x5)&= 3\\ {\log}_2(2(3x5))&= 3 \qquad \text{Apply the product rule of logarithms}\\ {\log}_2(6x10)&= 3 \qquad \text{Distribute}\\ 2^3&= 6x10 \qquad \text{Apply the definition of a logarithm}\\ 8&= 6x10 \qquad \text{Calculate } 2^3\\ 18&= 6x \qquad \text{Add 10 to both sides}\\ x&= 3 \qquad \text{Divide by 6} \end{align*}\]
USING THE DEFINITION OF A LOGARITHM TO SOLVE LOGARITHMIC EQUATIONS
For any algebraic expression \(S\) and real numbers \(b\) and \(c\),where \(b>0\), \(b≠1\),
\[\begin{align} {\log}_b(S)=c \text{ if and only if } b^c=S \end{align}\]
Example \(\PageIndex{9}\): Using Algebra to Solve a Logarithmic Equation
Solve \(2\ln x+3=7\).
Solution
\[\begin{align*} 2\ln x+3&= 7\\ 2\ln x&= 4 \qquad \text{Subtract 3}\\ \ln x&= 2 \qquad \text{Divide by 2}\\ x&= e^2 \qquad \text{Rewrite in exponential form} \end{align*}\]
Exercise \(\PageIndex{9}\)
Solve \(6+\ln x=10\).
 Answer

\(x=e^4\)
Example \(\PageIndex{10}\): Using Algebra Before and After Using the Definition of the Natural Logarithm
Solve \(2\ln(6x)=7\).
Solution:
\[\begin{align*} 2\ln(6x)&= 7\\ \ln(6x)&= \dfrac{7}{2} \qquad \text{Divide by 2}\\ 6x&= e^{\left (\dfrac{7}{2} \right )} \qquad \text{Use the definition of }\ln \\ x&= \dfrac{1}{6}e^{\left (\dfrac{7}{2} \right )} \qquad \text{Divide by 6} \end{align*}\]
Exercise \(\PageIndex{10}\)
Solve \(2\ln(x+1)=10\).
 Answer

\(x=e^5−1\)
Example \(\PageIndex{11}\): Using a Graph to Understand the Solution to a Logarithmic Equation
Solve \(\ln x=3\).
Solution
\[\begin{align*} \ln x&= 3\\ x&= e^3 \qquad \text{Use the definition of the natural logarithm} \end{align*}\]
Figure \(\PageIndex{3}\) represents the graph of the equation. On the graph, the xcoordinate of the point at which the two graphs intersect is close to \(20\). In other words \(e^3≈20\). A calculator gives a better approximation: \(e^3≈20.0855\).
Figure \(\PageIndex{3}\): The graphs of \(y=\ln x\) and \(y=3\) cross at the point \((e^3,3)\), which is approximately \((20.0855, 3)\).
Exercise \(\PageIndex{11}\)
Use a graphing calculator to estimate the approximate solution to the logarithmic equation \(2^x=1000\) to \(2\) decimal places.
 Answer

\(x≈9.97\)
Using the OnetoOne Property of Logarithms to Solve Logarithmic Equations
As with exponential equations, we can use the onetoone property to solve logarithmic equations. The onetoone property of logarithmic functions tells us that, for any real numbers \(x>0\), \(S>0\), \(T>0\) and any positive real number \(b\), where \(b≠1\),
\({\log}_bS={\log}_bT\) if and only if \(S=T\).
For example,
If \({\log}_2(x−1)={\log}_2(8)\), then \(x−1=8\).
So, if \(x−1=8\), then we can solve for \(x\),and we get \(x=9\). To check, we can substitute \(x=9\) into the original equation: \({\log}_2(9−1)={\log}_2(8)=3\). In other words, when a logarithmic equation has the same base on each side, the arguments must be equal. This also applies when the arguments are algebraic expressions. Therefore, when given an equation with logs of the same base on each side, we can use rules of logarithms to rewrite each side as a single logarithm. Then we use the fact that logarithmic functions are onetoone to set the arguments equal to one another and solve for the unknown.
For example, consider the equation \(\log(3x−2)−\log(2)=\log(x+4)\). To solve this equation, we can use the rules of logarithms to rewrite the left side as a single logarithm, and then apply the onetoone property to solve for \(x\):
\[\begin{align*} \log(3x2)\log(2)&= \log(x+4)\\ \log \left (\dfrac{3x2}{2} \right )&= \log(x+4) \qquad \text{Apply the quotient rule of logarithms}\\ \dfrac{3x2}{2}&= x+4 \qquad \text{Apply the one to one property of a logarithm}\\ 3x2&= 2x+8 \qquad \text{Multiply both sides of the equation by 2}\\ x&= 10 \qquad \text{Subtract 2x and add 2} \end{align*}\]
To check the result, substitute \(x=10\) into \(\log(3x−2)−\log(2)=\log(x+4)\).
\[\begin{align*} \log(3(10)2)\log(2)&= \log((10)+4) \\ \log(28)\log(2)&= \log(14)\\ \log \left (\dfrac{28}{2} \right )&= \log(14) \qquad \text{The solution checks} \end{align*}\]
USING THE ONETOONE PROPERTY OF LOGARITHMS TO SOLVE LOGARITHMIC EQUATIONS
For any algebraic expressions \(S\) and \(T\) and any positive real number \(b\), where \(b≠1\),
\[\begin{align} b^S=b^T\text{ if and only if } S=T \end{align}\]
Note, when solving an equation involving logarithms, always check to see if the answer is correct or if it is an extraneous solution.
How to: Given an equation containing logarithms, solve it using the onetoone property
 Use the rules of logarithms to combine like terms, if necessary, so that the resulting equation has the form \({\log}_bS={\log}_bT\).
 Use the onetoone property to set the arguments equal.
 Solve the resulting equation, \(S=T\), for the unknown.
Example \(\PageIndex{12}\): Solving an Equation Using the OnetoOne Property of Logarithms
Solve \(\ln(x^2)=\ln(2x+3)\).
Solution
\[\begin{align*} \ln(x^2)&= \ln(2x+3)\\ x^2&= 2x+3 \qquad \text{Use the onetoone property of the logarithm}\\ x^22x3&= 0 \qquad \text{Get zero on one side before factoring}\\ (x3)(x+1)&= 0 \qquad \text{Factor using FOIL}\\ x3&= 0 \qquad \text{or } x+1=0 \text{ If a product is zero, one of the factors must be zero}\\ x=3 \qquad \text{or} \\ x&= 11 \qquad \text{Solve for x} \end{align*}\]
Analysis
There are two solutions: \(3\) or \(−1\). The solution \(−1\) is negative, but it checks when substituted into the original equation because the argument of the logarithm functions is still positive.
Exercise \(\PageIndex{12}\)
Solve \(\ln(x^2)=\ln1\).
 Answer

\(x=1\) or \(x=−1\)
Solving Applied Problems Using Exponential and Logarithmic Equations
In previous sections, we learned the properties and rules for both exponential and logarithmic functions. We have seen that any exponential function can be written as a logarithmic function and vice versa. We have used exponents to solve logarithmic equations and logarithms to solve exponential equations. We are now ready to combine our skills to solve equations that model realworld situations, whether the unknown is in an exponent or in the argument of a logarithm.
One such application is in science, in calculating the time it takes for half of the unstable material in a sample of a radioactive substance to decay, called its halflife. Table \(\PageIndex{1}\) lists the halflife for several of the more common radioactive substances.
Substance  Use  Halflife 

gallium67  nuclear medicine  80 hours 
cobalt60  manufacturing  5.3 years 
technetium99m  nuclear medicine  6 hours 
americium241  construction  432 years 
carbon14  archeological dating  5,715 years 
uranium235  atomic power  703,800,000 years 
We can see how widely the halflives for these substances vary. Knowing the halflife of a substance allows us to calculate the amount remaining after a specified time. We can use the formula for radioactive decay:
\[\begin{align} A(t)&= A_0e^{\tfrac{\ln(0.5)}{T}t}\\ A(t)&= A_0e^{\tfrac{\ln(0.5)t}{T}}\\ A(t)&= A_0{(e^{\ln(0.5)})}^{\tfrac{t}{T}}\\ A(t)&= A_0{\left (\dfrac{1}{2}\right )}^{\tfrac{t}{T}}\\ \end{align}\]
where
 \(A_0\) is the amount initially present
 \(T\) is the halflife of the substance
 \(t\) is the time period over which the substance is studied
 \(y\) is the amount of the substance present after time \(t\)
Example \(\PageIndex{13}\): Using the Formula for Radioactive Decay to Find the Quantity of a Substance
How long will it take for ten percent of a \(1000\)gram sample of uranium235 to decay?
Solution
\[\begin{align*} y&= 1000e^{\tfrac{\ln(0.5)}{703,800,000}t}\\ 900&= 1000e^{\tfrac{\ln(0.5)}{703,800,000}t} \qquad \text{After } 10\% \text{ decays, 900 grams are left}\\ 0.9&= e^{\tfrac{\ln(0.5)}{703,800,000}t} \qquad \text{Divide by 1000}\\ \ln(0.9)&= \ln \left (e^{\tfrac{\ln(0.5)}{703,800,000}t} \right ) \qquad \text{Take ln of both sides}\\ \ln(0.9)&= \dfrac{\ln(0.5)}{703,800,000}t \qquad \ln(e^M)=M\\ t&= 703,800,000\times \dfrac{\ln(0.9)}{\ln(0.5)} \qquad \text{years Solve for t}\\ t&\approx 106,979,777 \qquad \text{years} \end {align*} \]
Analysis
Ten percent of \(1000\) grams is \(100\) grams. If \(100\) grams decay, the amount of uranium235 remaining is \(900\) grams.
Exercise \(\PageIndex{13}\)
How long will it take before twenty percent of our 1000gram sample of uranium235 has decayed?
 Answer

\(t=703,800,000×\dfrac{\ln(0.8)}{\ln(0.5)}\)years ≈ 226,572,993 years.
Media
Access these online resources for additional instruction and practice with exponential and logarithmic equations.
Key Equations
Onetoone property for exponential functions  For any algebraic expressions \(S\) and \(T\) and any positive real number \(b\), where \(b^S=b^T\) if and only if \(S=T\). 
Definition of a logarithm  For any algebraic expression S and positive real numbers \(b\) and \(c\), where \(b≠1\), \({\log}_b(S)=c\) if and only if \(b^c=S\). 
Onetoone property for logarithmic functions  For any algebraic expressions \(S\) and \(T\) and any positive real number \(b\), where \(b≠1\), \({\log}_bS={\log}_bT\) if and only if \(S=T\). 
Key Concepts
 We can solve many exponential equations by using the rules of exponents to rewrite each side as a power with the same base. Then we use the fact that exponential functions are onetoone to set the exponents equal to one another and solve for the unknown.
 When we are given an exponential equation where the bases are explicitly shown as being equal, set the exponents equal to one another and solve for the unknown. See Example \(\PageIndex{1}\).
 When we are given an exponential equation where the bases are not explicitly shown as being equal, rewrite each side of the equation as powers of the same base, then set the exponents equal to one another and solve for the unknown. See Example \(\PageIndex{2}\), Example \(\PageIndex{3}\), and Example \(\PageIndex{4}\).
 When an exponential equation cannot be rewritten with a common base, solve by taking the logarithm of each side. See Example \(\PageIndex{5}\).
 We can solve exponential equations with base \(e\),by applying the natural logarithm of both sides because exponential and logarithmic functions are inverses of each other. See Example \(\PageIndex{6}\) and Example \(\PageIndex{7}\).
 After solving an exponential equation, check each solution in the original equation to find and eliminate any extraneous solutions. See Example \(\PageIndex{8}\).
 When given an equation of the form \({\log}_b(S)=c\), where \(S\) is an algebraic expression, we can use the definition of a logarithm to rewrite the equation as the equivalent exponential equation \(b^c=S\), and solve for the unknown. See Example \(\PageIndex{9}\) and Example \(\PageIndex{10}\).
 We can also use graphing to solve equations with the form \({\log}_b(S)=c\). We graph both equations \(y={\log}_b(S)\) and \(y=c\) on the same coordinate plane and identify the solution as the xvalue of the intersecting point. See Example \(\PageIndex{11}\).
 When given an equation of the form \({\log}_bS={\log}_bT\), where \(S\) and \(T\) are algebraic expressions, we can use the onetoone property of logarithms to solve the equation \(S=T\) for the unknown. See Example \(\PageIndex{12}\).
 Combining the skills learned in this and previous sections, we can solve equations that model real world situations, whether the unknown is in an exponent or in the argument of a logarithm. See Example \(\PageIndex{13}\).
Contributors
 Lynn Marecek (Santa Ana College) and MaryAnne AnthonySmith (formerly of Santa Ana College). This content produced by OpenStax and is licensed under a Creative Commons Attribution License 4.0 license.